PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION BERBANTUAN MEDIA FLIPBOOK TERHADAP PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN DI SEKOLAH DASAR - Wanda Hamidah; Sofyan Iskandar; Dede Wahyudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In the learning process, students' success in participating in learning activities is greatly influenced by their reading ability. In this case, it means that reading is a strong foundation that students must have in the learning process. One of the problems faced in the world of education is the low level of reading comprehension ability. The aim of this research is to determine the ability to read and comprehend the influence and before and after the implementation of the Student Teams Achievement Division type cooperative learning model with the help of flipbook media in elementary school students. This research was carried out in the experimental class and control class at SD Negeri Aren Jaya IV. The method used in this research is quantitative. The type of research used was a quasi experiment with a non-equivalent control group design. Based on the research conducted, the conclusion was that the increase in reading comprehension skills of elementary school students in the experimental class was better than the control class, with a score for the experimental class of 80.00 and the control class of 72.73.   Keywords: flipbook media, reading comprehension, student Teams Achievement division learning model